Poetry therapy as intervention strategy in the post-divorce adjustment of adolescent girls - Hoek, Francilié (University of the Free State, 2005)
Divorce is one of the most traumatic and complex mental health crises facing children today. The purpose of this research study was to evaluate the influence of an intervention programme on the adjustment of adolescent girls from divorced families. A literature study was done and an empirical investigation utilizing the Personal, Home, Social and Formal Relations Questionnaire was conducted. Two groups, an experimental and control group, both consisting of six adolescents, were evaluated before and after the experimental group took part in a Poetry Therapy intervention programme. Criteria for inclusion were adolescent girls whose mother tongue is Afrikaans and whose parents were divorced. The eight-week programme was divided into five modules structured around the micro-maps of narrative therapy and focused on the exploration of identity, conflicting emotions, social integration and adapting to a changed environment. Poetry Therapy had a significant influence on the Personal Freedom scale of the Personal, Home, Social and Formal Relations Questionnaire, but not on the other adjustment scales. Poems written towards the end of the programme depict a sense of newfound connectedness, humour and the spirit of self-discovery. Participants further described a new-found confidence in their creative ability as well as a greater awareness of the contribution poetry can make in their lives. A limitation pertaining to this study was the small number of participants, as well as their availability after school hours to attend sessions. It is recommended that in future, a Poetry Therapy programme be presented in an in-house facility where clients are available for sessions at all times. More research is needed, especially cross-culturally, to determine what populations benefit and to what degree. The employment of Poetry Therapy as a preventative therapy needs to be explored.
Thesis (M.Soc.Sc. (Counselling Psychology))--University of the Free State, 2005
Keywords: Poetry -- Therapeutic use; Creative writing; Children of divorced parents -- Psychological aspects; Group intervention programme; Personal; Home; Social and formal relations questionnaire; Narrative therapy; Personal freedom scale; Confidence; In-house facility